The role of social media in enhancing adolescents’ digital life quality- survey study in the UAE - Tarek Ismail Mohamed; Ayman Ramdan Zhran; Nassereldin Abdel Qadir Osman; Amal Nabil Badr (International Journal of Adolescence and Youth)
The study aims to investigate the effect of social media on adolescents’ digital life quality based on the descriptive analytical approach. It includes two questionnaires about using social media and the quality of digital life. Participants (N = 192) are adolescents residing in the UAE who study in middle and high schools and range in age from 13 to 16. They come from Dubai, Sharjah, Ajman, Umm Al Quwain, and Ras Al-Khaimah Emirates. Findings show the significant role of social media in enhancing adolescents’ Digital Quality of Life. Findings also indicate statistically significant differences between respondents’ interests when using media applications in favour of those with scientific interests; they score the highest mean, 4.62. Also, there are statistically significant differences between the respondents when choosing their favourite means of communication; the differences favour Facebook by an arithmetic mean of 4.50, TikTok 4.39, Instagram 4.26, X 3.88, and Telegram 3.79.